2021
DOI: 10.36253/phyto-12135
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and identification of luteovirids affecting chickpea in Sudan

Abstract: In Sudan yellowing viruses are key production constraints in pulse crops. Field surveys were carried out to identify luteovirids affecting chickpea crops in the major production regions (Gezira Scheme and River Nile State). A total of 415 chickpea plant samples with yellowing and stunting symptoms were collected during the 2013, 2015 and 2018 growing seasons. Serological results (Tissue-blot immunoassays) showed that Luteoviridae and Chickpea chlorotic dwarf virus (CpCDV, genus Mastrevirus, family Geminivirida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…CLRDV research has grown at a rapid rate due in part to the spread of the virus to new regions including the US; however, the base assumption on the causative agent of CBD in Africa being CLRDV needs to be addressed (19). The lack of genetic evidence from CBD presenting cotton samples from Africa as well as potential conflicting reports concerning the origin between South America and Brazil raises reasonable doubt on the etiological connection between South American and African CBD (3,4,12,15). Furthermore, while the broad symptomology and aphid transmission similarities support the idea of a shared causative agent, these factors alone are not definitive for classifying the etiological agent (1).…”
Section: Discussionmentioning
confidence: 99%
“…CLRDV research has grown at a rapid rate due in part to the spread of the virus to new regions including the US; however, the base assumption on the causative agent of CBD in Africa being CLRDV needs to be addressed (19). The lack of genetic evidence from CBD presenting cotton samples from Africa as well as potential conflicting reports concerning the origin between South America and Brazil raises reasonable doubt on the etiological connection between South American and African CBD (3,4,12,15). Furthermore, while the broad symptomology and aphid transmission similarities support the idea of a shared causative agent, these factors alone are not definitive for classifying the etiological agent (1).…”
Section: Discussionmentioning
confidence: 99%
“…The known vector continues to be A. gossypii , and losses associated with ACBD are significantly lower when compared to CDB ( Hoffmann et al, 2019 ). Between 2012 and 2021, India ( Mukherjee et al, 2012 ), Thailand ( Sharman et al, 2015 ), Timor-Leste ( Ray et al, 2016 ), Sudan ( Kumari et al, 2020 ), Uzbekistan ( Moukahel et al, 2021 ), and Australia ( Davis et al, 2021 ) have reported CLRDV.…”
Section: The Viral Threat In Cottonmentioning
confidence: 99%
“…Important luteoviruses were detected in cotton in Australia ( Ellis et al, 2013 ) and Argentina, respectively, called Cotton bunchy top virus, CBTV, and Cotton leafroll bushy virus (CLRBV). CLRDV has been reported in Brazil ( Correa et al, 2005 ), Argentina ( Distéfano et al, 2010 ), India ( Mukherjee et al, 2012 ), Thailand ( Sharman et al, 2015 ), Timor-Leste ( Ray et al, 2016 ), Uzbekistan ( Moukahel et al, 2021 ), and Sudan ( Kumari et al, 2020 ). Furthermore, it has been reported in various states in North America, first in Alabama ( Avelar et al, 2019 ), and later in Mississippi ( Aboughanem-Sabanadzovic et al, 2019 ), Georgia ( Tabassum et al, 2019 ), Texas ( Alabi et al, 2020 ), Kansas ( Ali and Mokhtari, 2020 ), and Florida ( Iriarte et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%